Aerodynamics modelling of floating offshore wind turbines - Singapore Wala, Abdulqadir Aziz (2017)
An unsteady Blade Element Momentum (uBEM) method is presented for the analysis of Floating Offshore Wind Turbines (FOWTs). FOWTs allow wind turbines to be placed in deeper waters with stronger and more consistent winds. However, the floating platform motions result in motions of the wind turbine not found in fixed-bottom wind turbines, thus the widely-used blade element momentum (BEM) method, a static analysis method, cannot be used to calculate wind turbine blade forces.